2008
DOI: 10.1007/s11104-008-9616-2
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of tomato (Lycopersicon esculentum Mill.) plant growth by rhizosphere competent 1-aminocyclopropane-1-carboxylic acid deaminase-producing streptomycete actinomycetes

Abstract: The ability of streptomycete actinomycetes to promote growth of tomato through the production of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase was evaluated under gnotobiotic and greenhouse conditions. To achieve this, 64 isolates of Streptomyces spp. obtained from a tomato rhizosphere in the United Arab Emirates were initially selected for their ability to produce ACC deaminase as well as indole-3-acetic acid (IAA) and subsequently for their rhizosphere competence as root colonizers. Of the two select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(132 citation statements)
references
References 54 publications
9
120
0
3
Order By: Relevance
“…Arka Kalyan) at osmotic potentials up to -0.8 MPa. El-Tarabily (2008) showed that ACC deaminase producing Streptomyces filipinensis 15 and S. atrovirens 26 could reduce tomato endogenous ACC levels in both roots and shoots, resulting in increased plant growth. Similarly, Palaniyandi et al (2013) also showed that some Streptomyces spp.…”
Section: Pgp Actinobacteria As Stress Relieversmentioning
confidence: 99%
“…Arka Kalyan) at osmotic potentials up to -0.8 MPa. El-Tarabily (2008) showed that ACC deaminase producing Streptomyces filipinensis 15 and S. atrovirens 26 could reduce tomato endogenous ACC levels in both roots and shoots, resulting in increased plant growth. Similarly, Palaniyandi et al (2013) also showed that some Streptomyces spp.…”
Section: Pgp Actinobacteria As Stress Relieversmentioning
confidence: 99%
“…The application of Streptomyces filipinensis no. 15, a 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase and IAA producer, reduced the endogenous levels of ACC, the immediate precursor of ethylene, in both roots and shoots and subsequently enhanced plant fitness to the environment [128]. Plant growth-promoting and stress-alleviating activities have been demonstrated for a halo-tolerant and ACC deaminase-producing Streptomycete sp.…”
Section: Bioprotectionmentioning
confidence: 99%
“…The efficacy of Streptomyces strains for PGP is extensively reported (Nassar et al 2003;El-Tarabily 2008;Gopalakrishnan et al 2012a, b). The soil biological activities and mineral nutrients (including microbial biomass carbon and nitrogen, dehydrogenase, total N, available P and % organic carbon) in the Streptomyces-treated rice plots, at harvest, were also found significantly higher over the untreated control plots.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces are a group of Gram-positive bacteria, with high G + C content belonging to the order Actinomycetales, which form branched mycelia and hence sometimes been classified as fungi imperfecti. Plant growth promotion potential of Streptomyces was reported on bean (Nassar et al 2003), tomato (El-Tarabily 2008), pea (Tokala et al 2002), wheat (Sadeghi et al 2012) and rice (Gopalakrishnan et al 2012a, b). Streptomyces promote plant growth either by producing indole-3-acetic acid (Aldesuquy et al 1998) or siderophores (Tokala et al 2002).…”
Section: Introductionmentioning
confidence: 99%